Treatment of basal cell carcinoma with Sonidegib and literature review - Ziyue JIA; Zhe ZHUANG; Xinhui LI; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the efficacy and safety of Sonidegib for basal cell carcinoma. Methods Clinical data and skin histology were analyzed in a patient with ulcerated brown plaque on the nasal dorsum. After the diagnosis of basal cell carcinoma, patient was orally given a Hedgehog pathway inhibitor, Sonidegib. Results The patient was diagnosed with basal cell carcinoma. After the treatment with Sonidegib, the skin lesions became flat and ulcers were healed, without the development of new ulcers. Prior to the treatment, patient's liver and muscle enzymes were normal. Following one-week treatment with Sonidegib, the patient experienced muscle weakness, loss of appetite, vomiting, fatigue, and drowsiness, with an EGOG level of 3. After 4 weeks of treatment, the liver enzymes and serum CK were 2.5 times over normal levels. Sonidegib was discontinued at week 6 due to his intolerance of side effects. Then the patient was given the Mohs surgery and skin grafting. Conclusions Sonidegib can induce liver damage and musculoskeletal reactions. Adverse reactions should be dynamically monitored in clinical use of this drug. If the tumor is large or direct surgical removal may cause severe trauma, neoadjuvant therapy can be beneficial. In clinic, drugs can be intermittently administered according to patients' tolerance to improve tolerance and adherence.